PENILAIAN RISIKO PADA PROSES PEMBUATAN SHEAR WALL PADA PEMBANGUNGAN APARTEMEN - Ade Jiwantyo Harjono (The Indonesian Journal of Occupational Safety and Health, 2017)
Based on data from the Ministry of Manpower and Transmigration at 2009 construction sector was the highest place occupational injuries. Worker in the process of manufacture shear wall at surabaya apartment  should work at altitude. Working at altitudeis a workthat possess fatal impact in the event of an accident. Thus risk assessment is needed as one way to reduce the number of workplace accidents. The research was a descriptive-observational research usingcross-sectionalstudy design. In this research,risk assessment was used qualitative methods. In the process of  risk assessment, hazard identification performed by using the Job Safety Analysis (JSA) and then risk assessment was conducted use a risk matrix, so that the level of risk on the job of making shear wall could be known.The residual risk assessment was performed using guidelines calculation control. The process of making shear wall is divided into four working steps, like installation of concrete bones, installation of form work, casting, and dismantling form work.Result of risk assessment is pure risks of falling from height and strucked by fallen material were 15, hand being wedged were 9, irritation and being hit were 4.There is still a residual risk on falling from height and strucked by fallen material were 3, hazards of hands being wedged were 2, irritation and being hit had residual risk as many as 1. Hazards identified were dropped from height, strucked by fallen materials, wedged, irritated,and being hit. Risk assessment in existencefor dropped from height and strucked by fallen material had a high risk, moderate risk for hands being wedged, being hitand  irritation had a low risk. While the residual risks that existed in all of  these risks were low. Keywords: hazard identification, risk assessment, residual risk